Pollen Viability of Aeschynanthus tricolor Hook. - Vitri Garvita Gandadikusumah; Hary Wawangningrum; Sri Rahayu (Journal of Tropical Life Science, 2017)
Aeschynanthus (Gesneriaceae) is climbing or trailing epiphytes from the tropical forests of South-East Asia. Several species are widely cultivated for their attractive flowers, which usually scarlet with long corolla tubes and probably bird pollinated.This study was carried out on Aeschynanthus tricolor Hook. to determine in vitro germinability of (1) pollen collected from flowers at anthesis, on the day before anthesis, or up to five days after anthesis and (2) pollen collected on the day of anthesis and then stored at -20oC for 127 days. Germinability tests were carried out on pollen grains after stored for four hours in 10% sucrose solution. The highest in vitro germination percentage observed was pollen collected on the day of anthesis (96.3%) and the lowest was pollen collected on the fifth day after anthesis (5.6%). The germination percentage of pollen after stored at -20oC was 98% at beginning and 22% after 127 days. From this research we can conclude that pollen of A. tricolor can be successfully collected and then stored for some time, will be practical benefit for plant breeding and conservation purposes.